2010
DOI: 10.1303/aez.2010.59
|View full text |Cite
|
Sign up to set email alerts
|

Full-sib reconstruction in haplodiploid populations

Abstract: Estimating colony numbers of invading Bombus terrestris in Japan is the most urgent task for eradicating the alien invasive species. Nests of bumble bees are hardly found in nature. A prospective alternative is estimating the number of nests with polymorphic genetic data of individuals foraging in the field. Full-sib reconstruction from such genetic data is NP-hard in a strict sense, but several heuristic methods have been proposed. Among them, likelihood methods have been often applied for reconstructing full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…We also found that sibship frequency‐based estimates of the effective number of breeders were consistent across sample years and had overlapping confidence intervals with estimates based on linkage disequilibrium, another commonly employed single‐sample N b estimator. The value of estimating counts of parents and family groups through sibship reconstruction has been demonstrated in other systems, such as monitoring abundance of social bee colonies by identifying sisters among foraging workers and estimating the number of female sea turtles (green [ Chelonia mydas ] and Kemp's ridley [ Lepidochelys kempii ] sea turtles) laying multiple clutches per season at the same nesting site (Toquenaga and Kokuvo ; Frey et al , ; Geib et al ). Fisheries and aquaculture systems have used similar methods to shed light on genetic variability between age stages, assess stocking strategies, and reconstruct putative parental genotypes among externally fertilized species (Liu and Ely , Li et al , Meraner et al , Hasanat et al ).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that sibship frequency‐based estimates of the effective number of breeders were consistent across sample years and had overlapping confidence intervals with estimates based on linkage disequilibrium, another commonly employed single‐sample N b estimator. The value of estimating counts of parents and family groups through sibship reconstruction has been demonstrated in other systems, such as monitoring abundance of social bee colonies by identifying sisters among foraging workers and estimating the number of female sea turtles (green [ Chelonia mydas ] and Kemp's ridley [ Lepidochelys kempii ] sea turtles) laying multiple clutches per season at the same nesting site (Toquenaga and Kokuvo ; Frey et al , ; Geib et al ). Fisheries and aquaculture systems have used similar methods to shed light on genetic variability between age stages, assess stocking strategies, and reconstruct putative parental genotypes among externally fertilized species (Liu and Ely , Li et al , Meraner et al , Hasanat et al ).…”
Section: Discussionmentioning
confidence: 99%
“…For social insects, population size estimates derived from numbers of individuals counted in the wild misrepresents key population-level processes, because the colony is the reproductive unit. Thus, accurate estimates of colony numbers are crucial for species of conservation concerns, as they are used for the identi cation of drivers of species declines (e.g., correlating population status with land use history) (Maebe et al 2015), for the monitoring and eradication of invasive species (Toquenaga and Kokuvo 2010), and the development of plans for conservation actions and priorities (Hansen and Jensen 2005, Lepais et al 2010, McGrady et al 2021). Many social pollinator species are in decline, which underscores the importance of accurate estimations of colony abundance for these species (Powney et al 2019).…”
Section: Introductionmentioning
confidence: 99%